PENGARUH MOTIVASI, REWARD, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. CITRA BUMI SUMATERA KOTA PALEMBANG - Yeni Febrianti; Tien Yustini (JURNAL ILMIAH EDUNOMIKA, 2024)
This research was conducted to obtain empirical evidence regarding the influence of motivation, rewards and work environment on employee performance. This research uses quantitative methods and primary data in the form of questionnaires and analyzed by SPSS statistical tools by testing classical assumptions followed by hypothesis testing. This research was conducted at PT Citra Bumi Sumatra in 2023-2024. The results of this research show that motivation has a negative effect on employee performance. This result is due to the lack of optimal leadership at PT Citra Bumi Sumatra in providing motivation to their subordinates. Rewards do not have an influence on employee performance at PT Citra Bumi Sumatra, this is because the reward regulations are not in accordance with employee wishes. The work environment has a positive effect on employee performance at PT Citra Bumi Sumatra. This result is caused by the fact that the work environment, both physical and non-physical in the office, supports employees to be productive and improves employee performance at PT Citra Bumi Sumatra. Motivation, Reward and Work Environment together have a significant effect on employee performance. These results show that these three variables are related, and are in accordance with theory and previous research.